2014
DOI: 10.1007/s00213-014-3766-0
|View full text |Cite
|
Sign up to set email alerts
|

The VMAT-2 inhibitor tetrabenazine alters effort-related decision making as measured by the T-maze barrier choice task: reversal with the adenosine A2A antagonist MSX-3 and the catecholamine uptake blocker bupropion

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 93 publications
4
84
0
Order By: Relevance
“…Although classical stimulant medications that increase DA release and/or block DA reuptake increase motivation in rodent models Yohn et al, 2015), they have demonstrated only limited efficacy in chronically treating fatigue and other DA-related symptoms in trials for patients with cancer and other medical illnesses that are associated with inflammation (Bruera et al, 2013;Butler et al, 2007;Escalante et al, 2014;Gong et al, 2014;Mar Fan et al, 2008;Moraska et al, 2010;Pucci et al, 2007;Ruddy et As stimulants act to increase DA release and block DAT function to increase synaptic levels of available DA, these drugs may not provide long-term efficacy in the context of inflammation. As described in detail in the section 'Mechanisms of inflammation effects on dopamine synthesis and release' above, although some evidence exists that inflammation may reduce DA packaging and/or release, and decrease DA receptor signaling, the primary mechanism by which inflammation may impact DA transmission is by decreasing DA synthesis, which would lend to only a limited supply of available vesicular or cytosolic DA on which stimulants may act.…”
Section: Potential Therapeutic Targets For Inflammation Effects On Damentioning
confidence: 99%
See 1 more Smart Citation
“…Although classical stimulant medications that increase DA release and/or block DA reuptake increase motivation in rodent models Yohn et al, 2015), they have demonstrated only limited efficacy in chronically treating fatigue and other DA-related symptoms in trials for patients with cancer and other medical illnesses that are associated with inflammation (Bruera et al, 2013;Butler et al, 2007;Escalante et al, 2014;Gong et al, 2014;Mar Fan et al, 2008;Moraska et al, 2010;Pucci et al, 2007;Ruddy et As stimulants act to increase DA release and block DAT function to increase synaptic levels of available DA, these drugs may not provide long-term efficacy in the context of inflammation. As described in detail in the section 'Mechanisms of inflammation effects on dopamine synthesis and release' above, although some evidence exists that inflammation may reduce DA packaging and/or release, and decrease DA receptor signaling, the primary mechanism by which inflammation may impact DA transmission is by decreasing DA synthesis, which would lend to only a limited supply of available vesicular or cytosolic DA on which stimulants may act.…”
Section: Potential Therapeutic Targets For Inflammation Effects On Damentioning
confidence: 99%
“…For instance, VMAT2 activity can be increased with the small molecule trkB agonist, 7,8-dihydroxyflavone, which was neuroprotective in a rodent model of PD (Jang et al, 2010). In addition to compounds that may increase DA availability and release, adenosine (A2A) receptor antagonists, which are thought to facilitate the activation of DA D2 receptors, are efficacious in reversing decreased effort-based sucrose consumption after DA depletion with tetrabenazine (a vesicular monoamine transporter inhibitor) and after peripheral administration of IL-1β in rats (Chen et al, 2001;Collins et al, 2010;Nunes et al, 2014;Xie et al, 2009;Yohn et al, 2015). The DA receptor agonist, pramipexole, has been shown to block endotoxin-induced degeneration of nigrostriatal DA cells (Iravani et al, 2008), and has also demonstrated the efficacy in unipolar and bipolar patients with treatment-resistant depression (Cassano et al, 2004;Cusin et al, 2013;Fawcett et al, 2016;Franco-Chaves et al, 2013).…”
Section: Strategies To Facilitate Da Packaging and Release Or Da Recementioning
confidence: 99%
“…Across multiple paradigms, low doses of DA antagonists and accumbens DA depletions reduce the tendency to work for high reward options and increase selection of low reward choices Correa 2002, 2012;Salamone et al, 2003Salamone et al, , 2007Floresco et al, 2008;Mai et al, 2012;Randall et al, 2012;Hosking et al, 2015). Recent studies have shown that reduced selection of high-effort alternatives in rodents is induced by manipulations associated with depression, including stress (Shafiei et al, 2012), proinflammatory cytokine administration , and injections of the vesicular monoamine transporter-type 2 (VMAT-2) inhibitor tetrabenazine (TBZ; Nunes et al, 2013;Randall et al, 2014;Yohn et al, 2015). TBZ induces depressive symptoms including fatigue in humans (Frank 2010), and recent studies show that this drug shifts choice behavior from high effort to low effort options at doses that do not impair intake of or preference for solid foods or sucrose, hedonic reactivity to sucrose, reference memory, or discrimination of reward magnitude (Nunes et al, 2013;Randall et al, 2014;Pardo et al, 2015;Yohn et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Processes involved in activational aspects of motivation promote the instigation and maintenance of behavior, increase energy expenditure, and facilitate the exertion of effort to overcome obstacles that separate organisms from significant stimuli Correa, 2002, 2012;Yohn et al, 2015). Motivational dysfunctions related to behavioral activation are probably the most common psychiatric symptoms in general medicine (Demyttenaere et al, 2005); symptoms such as anergia, fatigue, psychomotor retardation, or apathy, are frequently observed in people with depression, Parkinsonism, and other disorders (Demyttenaere et al, 2005;Fava et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation